PATOLOGI KELEMBAGAAN DEMOKRASI ELEKTORAL: KORUPSI POLITIK DI INDONESIA PASCA-REFORMASI - Noer, Hamka Hendra (President University, 2025)
The 1998 Reformasi represents a pivotal shift in Indonesia's political evolution, directing the nation towards electoral democracy with aspirations for transparent and accountable governance. However, this transition has paradoxically entrenched political corruption within the democratic framework rather than mitigating it. This article investigates political corruption as an institutional pathology inherent in electoral democracy, highlighting the influences of weak institutions, dependency on patronage, and a deficiency in political ethics that foster transactional practices within procedural democracy. The theoretical framework used is derived from Nye, Friedrich, and Philp, who conceptualize corruption as a socio-political phenomenon that surpasses legalistic definitions. A comparative analysis between developed and semi-democratic nations illustrates that the effectiveness of democracy in combating corruption is significantly contingent upon institutional consolidation, a deliberative political culture, and the presence of robust checks and balances. The findings suggest that post-Reformation of Indonesian democracy continues to grapple with issues of money politics, insufficient transparency in party financing, and weak accountability among political elites. The article argues that without comprehensive reforms—including enhanced regulatory measures, education in political ethics, and the empowerment of civil society—democracy risks degenerating into mere proceduralism that legitimizes corruption. This study contributes to the broader discourse on the intricate relationship between electoral democracy and corruption in developing countries.